Characterization of the Bacteriophage vB_VorS-PVo5 Infection on Vibrio ordalii: A Model for Phage-Bacteria Adsorption in Aquatic Environments - Echeverría-Vega, Alex; Morales-Vicencio, Pablo; Saez-Saavedra, Camila; Alvarez, María Alejandra; Gordillo, Felipe; Del-Valle, Rodrigo; Solís, Ma. Eugenia; Araya, Rubén (Frontiers in Microbiology, 2020)
A mathematical first-order difference equation was designed to predict the dynamics of the phage-bacterium adsorption process in aquatic environments, under laboratory conditions. Our model requires knowledge of bacteria and bacteriophage concentrations and the measurements of bacterial size and velocity to predict both the number of bacteriophages adsorbed onto their bacterial host and the number of infected bacteria in a given specific time. It does not require data from previously performed adhesion experiments. The predictions generated by our model were validated in laboratory. Our model was initially conceived as an estimator for the effectiveness of the inoculation of phages as antibacterial therapy for aquaculture, is also suitable for a wide range of potential applications.